Resistance and Endurance Exercise Training Induce Differential Changes in Gut Microbiota Composition in Murine Models - Fernández, Javier; Fernández-Sanjurjo, Manuel; Iglesias-Gutiérrez, Eduardo; Martínez-Camblor, Pablo; Villar, Claudio J.; Tomás-Zapico, Cristina; Fernández-García, Benjamin; Lombó, Felipe (Frontiers in Physiology, 2021)
The effect of resistance training on gut microbiota composition has not been explored, despite the evidence about endurance exercise. The aim of this study was to explore and compare the effect of resistance and endurance training on gut microbiota composition in mice. Cecal samples were collected from 26 C57BL/6N mice, divided into three groups: sedentary (CTL), endurance training on a treadmill (END), and resistance training on a vertical ladder (RES). After 2 weeks of adaption, mice were trained for 4 weeks, 5 days/week. Maximal endurance and resistance capacity test were performed before and after the training period. Genomic DNA was extracted from cecal content and 16S Ribosomal RNA sequenced for metagenomics analysis. The percentages for each phylum, class, order, family or genus/species were obtained using an open-source bioinformatics pipeline. END showed both higher diversity and evenness, as well as a significantly higher relative abundance of Desulfovibrio and Desulfovibrio sp. RES displayed higher relative abundance of Clostridium and C. cocleatum. Both END and RES mice showed significantly less relative abundance of Ruminococcus gnavus and a higher relative abundance of the genus Parabacteroides compared to CTL. We explored the relationship between relative taxa abundance and maximal endurance and resistance capacities after the training period. Lachnospiraceae and Lactobacillaceae families were negatively associated with endurance performance, while several taxa, including Prevotellaceae family, Prevotella genus, and Akkermansia muciniphila, were positively correlated. About resistance performance, Desulfovibrio sp. was negatively correlated, while Alistipes showed a positive correlation. Resistance and endurance training differentially modify gut microbiota composition in mice, under a high-controlled environment. Interestingly, taxa associated with anti- and proinflammatory responses presented the same pattern after both models of exercise. Furthermore, the abundance of several taxa was differently related to maximal endurance or resistance performance, most of them did not respond to training.